Antiproliferative Effect of Secang Heartwood Ethanolic Extract (Caesalpinia sappan L.) on HER2-Positive Breast Cancer Cells - Rahmawaty Rachmady; Laely Muntafiah; Fahmi Rosyadi; Imroatus Sholihah; Sri Handayani; Riris Istighfari Jenie (ISCC (Indonesian Journal of Cancer Chemoprevention), 2016)
Human Epidermal Growth Factor Receptor 2 (HER2) plays critical role in the initiation of breast cancer cell proliferation. Inhibition of HER2 overexpression is a promising strategy in the treatment of breast cancer. One of the potential natural substances that possess cytotoxic in cancer cells is Secang (Caesalpinia sappan L.). Ethanolic extract of secang heartwood containing brazilein and brazilin shows cytotoxic effect on various cancer cells. Thus this research aims to determine the proliferative inhibition activity of secang heartwood ethanolic extract (SEE) through HER2 expression on MCF-7/HER2 positive. Cytotoxic activity of SEE on MCF-7/HER2 positive cells was observed by MTT assay, meanwhile the inhibition activity of  HER2 on MCF-7/HER2 cells was determined by immunofluoresence assay. Furthermore, to confirm the possible mechanism of brazilein and brazilin for its cytotoxic activity was studied through molecular docking using PLANTS software. Based on this study, SEE exhibited cytotoxic effect on MCF-7/HER2 positive cells with IC50 value of 25 µg/ml, and EES also inhibited HER2 expression, indicated that the antiproliferative effect of SEE was possible through the inhibition of HER2. Docking score of brazilein, brazilin, and native ligand on HER2 were -77; -73; -120 respectively, showed the affinity of brazilein in HER2 was lower than affinity of native ligand, but they had specific amino acid to interaction. Hence, SEE can be developed as one of promising chemopreventive agent from natural products.